Is atmospheric convection organised?: information entropy analysis. Issue 5 (2nd November 2019) - Li, Yuanlong; Yano, Jun-Ichi; Lin, Yanluan
ABSTRACT: In order to quantify the degree of organisation of atmospheric convection, an analysis based on the information entropy, which is widely considered a measure of organisation in information science, is performed. Here, the information entropy is defined in terms of the spectrum of the empirical orthogonal functions (EOFs). Satellite-based brightness temperature data from CLAUS (Cloud Archive User Service) is used over the domain covering the Indian Ocean and the Western Pacific with a spatial resolution of 2 / 3 ∘ from January 1985 to June 2009. The information entropy remains close to a mean value of 0.899 with a very small standard deviation of 2.7 × 10 − 3, suggesting that the atmospheric convection is always disorganised under a measure of the information entropy, which is against our common understanding. To better interpret this result, some basic theoretical analyses are performed, and the values of the information entropy for different systems (English literature texts, turbulent flows) from previous studies are reviewed. The same analysis is further performed on the Ising model, which is characterised by a clustering tendency of spin distribution, akin to convective organisation morphologically, at the critical temperature. The study suggests a need for a careful use of the term "organised". Atmospheric convection represents a tendency for clustering up to the planetary scale in analogous manner as the critical-point behaviour of the Ising model. However, neither is considered an "ordered" state under a measure of the information entropy.